Flue gas deNOxing spent V2O5-WO3/TiO2 catalyst: A review of deactivation mechanisms and current disposal status. (15th April 2023) - Ding, Long; Wang, Yifan; Qian, Lixin; Qi, Pengyu; Xie, Meng; Long, Hongming
Highlights: Deactivation mechanism of SCR catalyst in the industrial flue gas was summarized. The production amount of spent catalyst in typical deNOx industries was given. Current research progress and challenges of spent catalyst treatment were reviewed. Treating spent catalyst by metallurgy has promising application and were advocated. Abstract: Human concerns about the pollution of oxynitride emissions in industrial flue gases led to a dramatic increase in the demand for V2 O5 -WO3 /TiO2 catalysts. However, the complex composition of industrial flue gas reduces the catalyst activity, and the catalyst eventually becomes hazardous waste. This work describes the poisoning mechanism of V2 O5 -WO3 /TiO2 catalysts and the number of spent catalysts generated in specific deNOxing industries. The dust, moisture, acid gases, alkali metals, and heavy metals contained in flue gas can damage the working environment of the catalyst through physical and chemical action, reducing the catalyst's activity. For spent catalyst, the current research progress and challenges are reviewed from three aspects: activity regeneration, harmless disposal, and resource utilization. Regeneration can restore the activity of the catalyst, but the regeneration times are limited. The harmless disposal cannot maximize the valuable of resources. Wet recoveries of valuable metals are still in the laboratory or pilot stage. Environmental issues are still the current technical bottleneck for spent catalyst utilization. To achieve efficient and clean utilization of the fundamental component of spent catalysts, this work timely analyzes the current status of research on technologies related to the disposal and resource utilization of spent catalysts in metallurgical processes. The prepared Ti-bearing products are employed in the blast furnace protection process, improving the economic efficiency and making the process more prospective for industrial applications. Meanwhile, optimizing process parameters for expanded applications and reducing the negative impact on the original production parameters need to be extensively investigated.